Combined effects of viscosity and surface roughness on electric submersible pump performance. (June 2017) - Siddique, MH; Samad, Abdus; Husain, Afzal
An electric submersible pump that lifts crude oil from well bore is a type of multi-stage centrifugal pump. The unexpected wellbore conditions like change in pumping fluid viscosity and sand production severely affect pump performance and eventually lead to breakdown. The present study proposes a numerical approach to understand the effects of fluid viscosity and surface roughness of the flow passages in an electric submersible pump at design and off-design conditions. A three-dimensional numerical analysis was carried out by solving Reynolds-averaged Navier–Stokes equations with shear stress transport turbulence model to characterize performance of the pump. The pumping fluids, i.e., water and crude oils of different viscosities were analyzed for different surface roughness ( Ks ) values. The model predictions were compared with a theoretical one-dimensional model for the effect of viscosity and surface roughness. It was found that the disc-friction and the skin-friction losses are sensitive hydraulic losses of which the disc-friction loss increases with increase in viscosity, whereas skin-friction loss decreases with increase in surface roughness at high viscosity. The combined effect of viscosity and roughness showed a complicated behavior and eventually an improvement in pump performance at a higher surface roughness compared to a smoother and lowers surface roughness.